1982
DOI: 10.1111/j.1151-2916.1982.tb10357.x
|View full text |Cite
|
Sign up to set email alerts
|

A Simple Method for Determining Elastic‐Modulus–to‐Hardness Ratios using Knoop Indentation Measurements

Abstract: A simple indentation technique for measuring the hardness‐to‐modulus ratio of elastic/plastic materials was developed. The method, which is based on measurement of the elastic recovery of the in‐surface dimensions of a Knoop indentation, allows ready evaluation of the hardness‐to‐modulus ratio to an accuracy better than 10%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
153
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 491 publications
(163 citation statements)
references
References 4 publications
6
153
1
3
Order By: Relevance
“…12,18 The useful load range is relatively limited, and the hardness variations due to load dependence will probably be small in comparison with variations caused by experimental errors. 20,21 Only Knoop hardness was significantly higher for superficial than for deep dentin. The chief characteristic of the Knoop hardness test is its sensitivity to surface effects and textures.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…12,18 The useful load range is relatively limited, and the hardness variations due to load dependence will probably be small in comparison with variations caused by experimental errors. 20,21 Only Knoop hardness was significantly higher for superficial than for deep dentin. The chief characteristic of the Knoop hardness test is its sensitivity to surface effects and textures.…”
Section: Discussionmentioning
confidence: 91%
“…12 For Knoop hardness, upon unloading, elastic recovery occurs mainly along the shortest diagonal and depth, but the longest diagonal remains relatively unaffected. 19,20 Therefore, the hardness measurements obtained by this method are practically insensitive to the elastic recovery of the material.…”
Section: Discussionmentioning
confidence: 99%
“…La microdureza HV del recubrimiento fue hallada a partir de indentaciones realizadas con un indentador Vickers y el módulo de elasticidad fue calculado usando el método de Marshall [26], el cual se basa en el análisis de la huella residual producida con un indentador Knoop.…”
Section: Microindentaciónunclassified
“…In 1980, Marshall et al [12] suggested to evaluate the elastic modulus of a material by considering the elastic recovery of a Knoop indentation. These authors had observed that the small diagonal, w', of the indent was shorter than the expected theoretical value, w, while the large diagonal, L, remains constant after the withdrawal of the indenter.…”
Section: Elastic Modulusmentioning
confidence: 99%
“…The second objective is to examine the validity of the interpretation of indentation results obtained by various indentation process and indenters (Knoop, Vickers and sphere). For the determination of the elastic modulus, Knoop indentation will be used within the objective to apply the Marshall's method [12] based on the elastic recovery of the indent. Then Vickers and spherical indenters will be used to determine the elastic modulus in the conditions of calibration stated above.…”
Section: Introductionmentioning
confidence: 99%